Are Economic Preferences Shaped by the Family Context? The Impact of Birth Order and Siblings' Sex Composition on Economic Preferences - Lena Detlefsen; Andreas Friedl; Katharina Lima de Miranda; Ulrich Schmidt; Matthias Sutter (Center for Economic Studies and ifo Institute (CESifo), 2018)
The formation of economic preferences in childhood and adolescence has long-term consequences for life-time outcomes. We study in an experiment with 525 teenagers how both birth order and siblings' sex composition affect risk, time and social preferences. We find that second born children are typically less patient, less risk averse, and more trusting. However, siblings' sex composition interacts importantly with birth order effects. Second born children are more risk taking only with same-sex siblings. For trust and trustworthiness, birth order effects are larger with mixed-sex siblings than in the single-sex case. Only for patience, siblings' sex composition does not matter.
Keywords: C93; D10; D90; J12; 330; birth order; siblings' sex composition; economic preferences; experiment